2020
DOI: 10.5152/tjg.2014.4850
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of MR colonography using dark lumen technique for detection of colonic lesions

Abstract: Background/Aims: To assess the detectability of the lesions with magnetic resonance (MR) colonography using dark lumen technique that had been detected on conventional colonoscopy. Materials and Methods: A total of 38 patients who were suspected to have a colorectal mass between April 2008 and June 2010 were included in this prospective study. Warm tap water was administered via a rectal tube to the patients in prone position. Then, axial T2 true-fast imaging with steady-state precession (FISP), axial T2 half-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…This finding is supposed by the work of Hoffman et al but Beker et al finding differs from us but his study was included all type of lesion. 16,17 We have observed that for all size polyp sensitivity, specificity, positive predictive value, negative predictive value and accuracy was between 85.71% to 94.34%.For size above 8 mm all these value was 100% for size below 4 mm to 8 mm sensitivity was less and specificity was 97.44%. For size below 4 mm sensitivity was 28.57% and specificity was 92.31% but all parameter was less.…”
Section: Discussionmentioning
confidence: 87%
“…This finding is supposed by the work of Hoffman et al but Beker et al finding differs from us but his study was included all type of lesion. 16,17 We have observed that for all size polyp sensitivity, specificity, positive predictive value, negative predictive value and accuracy was between 85.71% to 94.34%.For size above 8 mm all these value was 100% for size below 4 mm to 8 mm sensitivity was less and specificity was 97.44%. For size below 4 mm sensitivity was 28.57% and specificity was 92.31% but all parameter was less.…”
Section: Discussionmentioning
confidence: 87%
“…МРТ ТК предусматривает заполнение кишки водой через введенный за связку Трейтца интестинальный зонд или per os. Используются методики «светлого просвета» (bright lumen), основанной на получении Т2-ВИ в быстрой импульсной последовательности, и «темного просвета» (dark lumen), основанной на получении Т1-ВИ с одновременным внутривенным введением контрастного вещества и динамическим контрастированием [17][18][19]. Ограничения МРТ в изучении ТК, помимо противопоказаний данного метода, опосредованы долгой «экспозицией» при получении среза и зависимости от перистальтики.…”
Section: оригинальные исследованияunclassified